PENGEMBANGAN INSTRUMEN PENILAIAN SIKAP PERCAYA DIRI DALAM PEMBELAJARAN BAGI SISWA SEKOLAH DASAR - Yuli Astuti Yuli Astuti; Pardimin; Ari Setiawan (Universitas Sarjanawiyata Tamansiswa, 2023)
The research objectives is to produce an instrument for assessing self-confidence in appropriate learning, knowing the quality of the assessment instrument, and knowing the results of the instrument that has been tested on students. This type of research is development research (Research & Development). The data collection technique for this research is a student self-assessment questionnaire with a cluster random sampling technique of 100 for limited trials and 150 for expanded trials. The results of the research show that the instrument for assessing self-confidence in learning that was developed is suitable for use with elementary school students. The results of the instrument validity test using Exploratory Factor Analysis (EFA) showed a KMO MSA value of 0.716, the results of the instrument reliability test using Cronbach's Alpha showed a reliability value of 0.758. These results prove that the self-confidence assessment instrument is valid and reliable. The results of the assessment on the application test of 53 students showed that the attitude of self-confidence in the aspect of self-ability was 86.79% entrenched and 13.21% developed, the attitude of self-confidence in the aspect of responsibility was 94.34% entrenched and 5.66% developed, the attitude of trust in the aspect of communication skills, 84.91% are cultured and 15.09% are developing.